88 - USE OF PROTEIN SUPLEMENTS BY PEOPLE ENGAGED IN PHYSICAL EXERCISE: THE RISKS AND BENEFITS (Fiep Bulletin - online, 2011)
Dietary supplements are ergogenic aids that can be used to improve performance and results in sporting activities and fitness programs, particularly bodybuilding. Protein and amino-acid based dietary supplements are among the most popular. Adequate availability of amino acids is not only crucial for increasing muscle fiber synthesis, but also in order to promote repair of damaged muscle tissue. However, additional consumption of these protein supplements beyond daily requirements does not result in additional muscle tissue being gained and neither does it lead to increased performance, but may in fact cause renal overload.
Keywords: Supplementation; protein; physical exercise